Ahmad Talib's Poetry in Persian Language: Formal and Lexicostylistic Features - Gačanin, Sabaheta (Prilozi za orijentalnu filologiju, 2017)
This paper represents an analysis of poetry by Ahmad Talib Bosniak in Persian language. The analysis is based on its formal features (half-verse, verse, poetic form, poetic strategy, rhyme and meter) and its lexicostylistic features (paradigmatic and associative meanings) as well, in order to evaluate its artistic and aesthetic impact which would contribute in determining the literary and historical context of the complete poetry in the frame of this poet. The analysis contains six Talib's ghazals and five kit'as in Persian language (text in Persian, transcription, translation and facsimiles).